Disease-specific gaps within fungal respiratory tract infections: clinical features, diagnosis, and management in critically ill patients. Issue 3 (11th May 2022) - Martin-Loeches, Ignacio; Nseir, Saad; Rodriguez, Alejandro; Azoulay, Elie
Abstract : Purpose of review: We aim to examine the most recent findings in the area of invasive pulmonary fungal infections to determine the appropriate/and or lack of prevention measures and treatment of upper fungal respiratory tract infections in the critically ill. Recent findings: This will be addressed by focusing on the pathogens and prognosis over different bedridden periods in ICU patients, the occurrence of invasive fungal respiratory superinfections in patients with severe coronavirus disease 2019 which has been recently noted following the SARS-CoV-2 pandemic. Relevant reports referenced within include randomized controlled trials, meta-analyses, observational studies, systematic reviews, and international guidelines, where applicable. Of note, it is clear there is a significant gap in our knowledge regarding whether bacterial and fungal infections in coronavirus disease 2019 are directly attributable to SARS-CoV-2 or a consequence of factors such as managing high numbers of critically unwell patients, and the prolonged duration of mechanical ventilation/ICU admission duration of stay. Summary: An optimal diagnostic algorithm incorporating fungal biomarkers and molecular tools for early and accurate diagnosis of Pneumocystis pneumonia, invasive aspergillosis, candidemia, and endemic mycoses continues to be limited clinically. There is a lack of standardized molecular approach to identify fungal pathogens directly in formalin-fixed paraffin-embedded tissues and suboptimal diagnostic approaches for mould blood cultures, tissue culture processing for Mucorales, and fungal respiratory cultures (i.e., the routine use of bronchoscopic examination in ICU patients with influenza-associated pulmonary aspergillosis) for fungal point-of-care testing to detect and identify new, emerging or underrecognized, rare, or uncommon fungal pathogens.